2003
DOI: 10.1172/jci200316887
|View full text |Cite
|
Sign up to set email alerts
|

Induction of immune tolerance to coagulation factor IX antigen by in vivo hepatic gene transfer

Abstract: Gene replacement therapy is an attractive approach for treatment of genetic disease, but may be complicated by the risk of a neutralizing immune response to the therapeutic gene product. There are examples of humoral and cellular immune responses against the transgene product as well as absence of such responses, depending on vector design and the underlying mutation in the dysfunctional gene. It has been unclear, however, whether transgene expression can induce tolerance to the therapeutic antigen. Here, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
252
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 377 publications
(261 citation statements)
references
References 44 publications
6
252
3
Order By: Relevance
“…20 Hepatic transduced mice failed to form antibody to hF.IX even after challenge with hF.IX protein formulated in complete Freund's adjuvant. After a second challenge with hF.IX in adjuvant, splenocytes from tolerized mice failed to proliferate after in vitro restimulation with hF.IX, while cells from naïve control mice showed hF.IX-specific proliferation after the repeated immunization.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…20 Hepatic transduced mice failed to form antibody to hF.IX even after challenge with hF.IX protein formulated in complete Freund's adjuvant. After a second challenge with hF.IX in adjuvant, splenocytes from tolerized mice failed to proliferate after in vitro restimulation with hF.IX, while cells from naïve control mice showed hF.IX-specific proliferation after the repeated immunization.…”
Section: Resultsmentioning
confidence: 97%
“…3,[16][17][18][19] This route of vector administration was found to induce immune tolerance to the F.IX transgene product. 20 Tolerance induction was favored by higher levels of F.IX expression and was associated with induction of regulatory CD4 + T cells that could suppress antibody formation to F.IX after adoptive transfer. 20 Tolerance induction was successful in several inbred strains of mice with different MHC haplotypes and in outbred mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…102 From recent studies using various gene transfer vectors, it seems that the use of liver specific promoters may be an ideal way to achieve efficient gene transfer to the liver in vivo without induction of immune response. 32,46 In that case, infection of antigen-presenting cells does not result in presentation of foreign peptides and impair transgene product-directed immune response. Other effective approaches to prevent immune response against the transduced cells are vector administration in utero and to newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies pointed out that these vectors may be tolerogenic to foreign proteins after delivery to the liver. 32 Moreover, they are relatively easy to prepare and clinical trials using this vector type have been performed or are still ongoing. Many studies have shown that AAV vectors are able to transduce hepatocytes for prolonged periods of time in animal models of various sizes.…”
Section: Aav Vectorsmentioning
confidence: 99%